Data Privacy in Multi Cloud Environment using Third Party Key Providence in Public Clouds (International Journal of Engineering and Computer Science, 2015)
Cloud computing provides the data to the users remotely on different services. The Encryption plays major role in securing the data in cloud. We can access the data using encryption with key for more privacy reasons. Now-a-days the public cloud needs more privacy because of the increment of number of users everyday. The multi cloud technique performs load balancing when there is huge transactions of the data. The key is used to arrange more security for accessing the data by the owner, but to have secure communication better to have a support of the third party for key issuing. In this paper we provide third party for key providing in multi cloud environment. The encryption algorithm provides basic security for the data